Relationship between stocks return and market return during festive season (Chinese New Year and Hari Raya) / Siti Zaiton Mohamad - Mohamad, Siti Zaiton (1995)
There are many factors contributing to the volatility of the stock prices. Certain events may related or influence the movement of the price. The purpose of the study is to examine whether there is an effect to Malaysian Stock Market during festive season particularly during Chinese New Year season and Hari Raya season. To be successful in their investment, the volatility of these stock markets has to be properly understood. So much so, the issue of price behaviour of these markets has become the focus of attention by both practitioners, investors and academicians.